Pediatric Headache: A Comprehensive Review - Arvinder Wander; Ankit Kumar Meena; Puneet Kumar Choudhary; Sameer Peer; Ramandeep Singh (Korean Child Neurology Society, 2024)
Pediatric headache is a common condition that often results in frequent outpatient visits. There are two broad etiological groups of headaches-primary and secondary headaches-with the former being more prevalent. Migraine, a type of primary headache, shares similarities with those experienced by adults, albeit with some variations in diagnostic criteria. The secondary causes of headache should be differentiated from the primary headaches with proper clinical evaluation and focussed investigations. The management of migraine focusses on lifestyle modifications, behavioral therapy, and pharmacotherapy for acute episodes and long-term preventive therapy. There are many novel promising treatment modalities. This review article provides an overview of pediatric headache epidemiology, classification, and pathophysiology and then elaborates on management and prevention strategies.